Drought-prone areas mapping using fuzzy c-means method in Gunungkidul district - Kismiantini, Kismiantini; Husniyah, Fajra; Montesinos-López, Osval Antonio (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2021)
Gunungkidul district is one of the districts in the Special Region of Yogyakarta that is frequently affected by drought disasters. The purpose of this study is to map drought-prone areas in Gunungkidul district using the fuzzy c-means method, making it easier for the government to allocate water-dropping assistance to drought-affected areas. The research variables include rainfall, soil type, infiltration, slope, and land use. The type of variables is an ordinal scale, so they must be transformed using the successive interval method before being analyzed using the fuzzy c-means method. The cluster validity indexes of the Xie and Beni index, partition coefficient, and modification partition coefficient were used to find the optimal k. The results of fuzzy c-means clustering revealed three clusters with a low level of vulnerability consisting of 7 sub-districts, a moderate level of vulnerability consisting of 8 sub-districts, and a high level of vulnerability consisting of 3 sub-districts. Rainfall, land use, soil type, infiltration, and slope were the drought hazard factors with the greatest to least effect in this study.